O parricídio como espetáculo da violência: O dia em que matei meu pai - Aileen El-Kadi (Estudos de Literatura Brasileira Contemporânea)
The first person narrative voice in the novel by Mario Sabino, O dia em que matei meu pai, builds an universe composed of two coordinates, one follows the logic of subjective pleasure/perversion where the characters show social pathology des- cribed by the narrator as a result of a context governed by psychological violence and amorality, and where the dynamics is always erotic, the other component is spectacular as the axis from which the characters seem to represent roles built based on stereotypes that arise from mass culture. The father’s murder by the protagonist and the way he confesses the crime at the beginning of the novel com- bine the two core values we find in the author’s aesthetic proposed: the amount of violence and spectacle for the representation of contemporary society.